2014
DOI: 10.1007/s10633-014-9439-9
|View full text |Cite
|
Sign up to set email alerts
|

A frequency-tagging electrophysiological method to identify central and peripheral visual field deficits

Abstract: A single electrode over Oz is sufficient to gather both central and peripheral visual signals and also to control for gaze deviation. Our method presents several advantages in evaluating visual fields integrity, as it is fast, reliable, and efficient, and applicable in children as young as 5 years old. However, a larger sample of healthy children should be tested to establish clinical norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The field-specific VEP had a sensitivity of 75% and a specificity of 87.5% [ 55 ]. This technique was further developed by Hébert-Lalonde et al [ 56 , 57 ] that used steady-state VEP and pattern ERG to field-specific radial checkerboards. They showed significantly lower responses to peripheral stimulations in the vigabatrin-exposed group, that were negatively correlated to vigabatrin exposure duration.…”
Section: Peripheral Visual-field Defectmentioning
confidence: 99%
“…The field-specific VEP had a sensitivity of 75% and a specificity of 87.5% [ 55 ]. This technique was further developed by Hébert-Lalonde et al [ 56 , 57 ] that used steady-state VEP and pattern ERG to field-specific radial checkerboards. They showed significantly lower responses to peripheral stimulations in the vigabatrin-exposed group, that were negatively correlated to vigabatrin exposure duration.…”
Section: Peripheral Visual-field Defectmentioning
confidence: 99%
“…Sorne authors suggest placing 3 electrodes, one at Oz, 01 and 02 (Odom et al, 2010), but a recent study indicated that there was no significant diff erence in information harvested from one to three electrodes. The electrode placed at 'Oz' gathered significantly higher signals in response to central visual stimulations, and recorded a similar signal in ail three electrodes for the peripheral visual stimulat~on (Hébert-Lalonde et al, 2014). Furthermore, using only one active electrode reduces electrode placement time, m~g it convenient for the population of interest.…”
Section: Electrode Placementmentioning
confidence: 95%
“…One method that has been explored and shows promise in its ability to detect visual field deficits is VEPs. Field-specific VEPs have been used to measure visual responses to central and peripheral visual stimuli (Harding, Robertson, & Holliday, 2000;Hébert-Lalonde et al, 2014;. Although this approach is useful for some populations, its current clinical application for children with OPGs is not optimal since field-specific VEPs are usually tested from transient VEPs (i.e., from low-rate abrupt stimulus presentations).…”
Section: Using Veps To Assess Visual Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Provided that the light conditions are carefully chosen (Herrmann, 2001;Norcia et al, 2015), and are kept constant throughout the trials, the stimulus elicits a detectable neural response, and if there are enough trials recorded, the amplitude of the frequency or frequencies corresponding to the stimulus will elevated in the spectrum of the SSVEP. The elevated frequencies may not always be the same as the temporal frequency of the stimulus (Hébert-Lalonde et al, 2014): it may be a harmonic (Norcia and Tyler, 1984) or if several temporal frequencies are used at the same time, they may produce intermodulational products (Baitch and Levi, 1988): the sum and difference of these frequencies, or an arbitrary combination of these. SSVEPs may be studied with techniques other than EEG as well, such as Magnetoencephalography (MEG) (Srinivasan et al, 1999) or functional Magnetic Resonance Imaging (fMRI) (Boremanse et al, 2013) as well.…”
Section: Introductionmentioning
confidence: 99%